2021
DOI: 10.1186/s12935-021-01861-8
|View full text |Cite
|
Sign up to set email alerts
|

Discovery and validation of PZP as a novel serum biomarker for screening lung adenocarcinoma in type 2 diabetes mellitus patients

Abstract: Background Patients with type 2 diabetes mellitus (T2DM) have an increased risk of suffering from various malignancies. This study aimed to identify specific biomarkers that can detect lung adenocarcinoma (LAC) in T2DM patients for the early diagnosis of LAC. Methods The clinical information of hospitalized T2DM patients diagnosed with various cancers was collected by reviewing medical records in Wuxi People’s Hospital Affiliated to Nanjing Medical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 35 publications
1
9
0
Order By: Relevance
“…The levels of 67 serum proteins were deemed remarkably different between these disease groups and the healthy participant group ( Figures 2A–C ). To redistribute the specimens based on similarities in the patterns of serum protein levels, we conducted a hierarchical cluster analysis of the 67 DAPs according to previous research ( Huang et al, 2010 ; Yang et al, 2021 ). Cluster analysis revealed a clear separation of the four groups ( Figure 2D ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The levels of 67 serum proteins were deemed remarkably different between these disease groups and the healthy participant group ( Figures 2A–C ). To redistribute the specimens based on similarities in the patterns of serum protein levels, we conducted a hierarchical cluster analysis of the 67 DAPs according to previous research ( Huang et al, 2010 ; Yang et al, 2021 ). Cluster analysis revealed a clear separation of the four groups ( Figure 2D ).…”
Section: Resultsmentioning
confidence: 99%
“…DIA-MS analysis was performed on each serum sample from the discovery set to obtain differential serum proteins. The main steps were as follows: protein extraction and FASP enzymatic hydrolysis, high PH RP classification, DDA-MS library construction and DIA analysis, these techniques were described in our previous publication ( Yang et al, 2021 ). DAPs were extracted using R language 4.0.0 with a criterion of fold change (FC) ≥ 1.50 or ≤0.67 and a unpaired t -test p value ≤0.05.…”
Section: Methodsmentioning
confidence: 99%
“…Recently, PZP has been described as a novel biomarker for screening lung adenocarcinoma in T2DM patients or predicting the prognosis of hepatocellular carcinoma. [ 56 , 57 ] However, It was noted that PZP expression is lower in tumor tissues than that in normal tissues [ 58 , 59 ] and ablation of PZP promotes breast cancer progression. [ 60 ] Thus, our protein therapy is safe without adverse effect in promoting tumor growth.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies found that PZP mRNA was downregulated in lung cancer tissues and was significantly correlated with immune cell infiltration. PZP as a new serum biomarker could identify lung adenocarcinoma in type 2 diabetes mellitus patients [ 37 ]. When proteomics was used to study the protein composition of plasma exosomes in healthy people, it was found that PZP protein was ubiquitous in exosomes [ 38 ], by which it could be delivered from donor cells to recipient cells, and regulated the function of recipient cells [ 8 ].…”
Section: Discussionmentioning
confidence: 99%
“…Our animal experiment showed that the content of PZP protein in colonic exosomes of IBD was significantly increased, which was consistent with the results of serum exosomes. On the other hand, IBD is characterized by uncontrolled activation of intestinal immune cells in a genetically susceptible host [ 42 ], and PZP was highly expressed in immune cells [ 37 ]. Our experiments partly confirmed our conjecture that there might be a correlation between exosomes in the colon and serum.…”
Section: Discussionmentioning
confidence: 99%